Influence of SEN depth and port angle on vertical electromagnetic brake effects in continuous casting mould. Issue 2 (6th March 2017) - Li, Zhuang; Wang, Engang; Xu, Yu; Xu, Lin
Abstract : Purpose: To effectively control the molten steel flow and the stability of free surface in continuous casting mould, this paper aims to propose a new type electromagnetic brake technique, namely, vertical electromagnetic brake (V-EMBr). Its brake effect under special processing parameters such as submerged entry nozzle (SEN) depth and port angle is evaluated by the numerical simulation methods. Design/methodology/approach: A couple three-dimensional mathematical model of fluid flow and static magnetic field was developed to investigate the behaviour of molten steel flow and steel/slag interface in the continuous casting mould, and a volume of fluid model is used to track the interfacial behaviour of molten steel and liquid slag by solving the continuity equation of the phase volume fraction. Findings: The simulation results showed that the application of V-EMBr can significantly reduce the flow intensity in upper recirculation zone and decrease the meniscus height and the flow velocity of molten steel in the vicinity of narrow side of mould, which is beneficial to reduce the possibility of mould flux entrapment. Especially, the brake effect of V-EMBr has a little affected by the SEN depth and port angle, which is helpful for V-EMBr to better adapt the actual continuous casting process. Originality/value: Compared to the conventional-level EMBr, the new proposed V-EMBr has the advantage to effectively control the molten steel flow and steel/slag interfacial fluctuation in the vicinity of narrow side of mould with a pair of magnetic fields, and its brake effect is less affected by the changes in continuous casting processing parameters.